Effect of neuropeptide Y on norepinephrine-induced constriction in the rabbit facial artery after carotid artery occlusion - Roganović, Jelena; Petrović, Nina; Djukić, Ljiljana (Vojnosanitetski pregled, 2014)
Background/Aim. Atherosclerotic-occlusive changes could be observed in orofacial branches of the external carotid artery. Atherosclerosis-induced ischemia caused alteration in production and release of endothelial factors. The aim of this study was to investigate the influence of carotid artery occlusion (10, 30 and 60 min) on vascular effects of norepinephrine (NOR) and neuropeptide Y (NPY) in the isolated glandular branch of the rabbit facial artery, the main feeding artery for the submandibular gland. Method. Changes in isometric tension were recorded in organ bath studies with arterial rings, before and after carotid artery occlusion. Results. Concentration-dependent vasocontractile effect of NOR was significantly augmented after 30 and 60 min of carotid occlusion, but only in the rings with intact endothelium. Given alone, NPY showed no effect in isolated glandular branch of the rabbit facial artery, but enhanced NOR vasoconstriction in all the investigated rings. NOR vasocontractile effect enhancement in the presence of NPY was attenuated after 30 and 60 min of carotid occlusion. Also, enhancement of NOR vasoconstriction by NPY was significantly higher in endothelium-intact rings compared to endothelium-denuded rings obtained after 30 and 60 min of carotid occlusion. Conclusion. The present investigation provides results of increased vasocontractile effect of NOR and decreased enhancing effect of NPY on NOR vasoconstriction in the rabbit facial artery after carotid occlusion that is related to altered endothelium function.